A review of China’s resources of lithium in coal seams - Chao Liu; Chao Liu; Chao Liu; Ting Zhao; Ting Zhao; Ting Zhao; Gaoshang Wang; Gaoshang Wang; Gaoshang Wang; Da Chen; Da Chen; Da Chen (Frontiers in Energy Research, 2024)
Lithium gains an increasing importance in new energy vehicles and stationary energy storage, and development and utilization of lithium mines has attracted great attention around the world. In addition to the traditional lithium resources, lithium resources in coal seams have great potential in industrial application. Therefore, how to develop and utilize them is strategically significant for guaranteeing supply of lithium resources in China and promoting clean energy transformation. This paper summarizes the metallogenic ages, occurrence, enrichment factors, availability of lithium resources in coal seams in China. Conclusion are obtained as follows. i. coal-hosted lithium deposits discovered in China so far mainly occur in the Carboniferous-Permian strata of North China. They are less concentrated in smaller range in the Permian strata of Qilian-Qinling. ii. In China, coal-hosted lithium is mainly enriched in aluminum-bearing minerals. Lithium in coal seams mainly occurs in the inorganic matter, and some occurs in the organic matter. iii. Lithium enrichment in coal seams is caused by stable supply of aluminum and lithium-bearing minerals and special structural and geological factors. iv. According to China’s national standards on grades of lithium content in coal seams, the metallogenic belts of lithium in coal seams at the southern foothill of Yin Shan and in Qilian-Qinling have the potential of lithium development and extraction, covering Junger mining area in Inner Mongolia, and Pingshuo and Ningwu mining areas in Shanxi.